2015
DOI: 10.2492/inflammregen.35.154
|View full text |Cite
|
Sign up to set email alerts
|

Induction of neural cells with spinal motoneuron phenotype from human iPS cells and the transplantation to totally transected spinal cords in mice

Abstract: Transplantation of neural cells is a promising therapeutic strategy for spinal cord injury (SCI). Here we generated neurons including those with spinal motoneuron phenotype from human induced pluripotent stem (hiPS) cells by leading to formation of embryoid bodies (EB) and subsequent adherent culture for 4 days during which retinoic acid (RA), noggin (NOG) and sonic hedgehog (SHH) were introduced twice. Spinal motoneuron specific HB9 mRNA expression remarkably increased in the presence of RA, NOG and SHH. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…We have already tested a variety of culture conditions employing different culture media and growth factors, and found that medium containing the defined amounts of the three factors (RA, NOG and SHH) were most suitable for inducing the differentiation into neurons including those with spinal motoneuron phenotype from hiPS cells [7].…”
Section: Induction Of Neural Differentiation Of Hips Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have already tested a variety of culture conditions employing different culture media and growth factors, and found that medium containing the defined amounts of the three factors (RA, NOG and SHH) were most suitable for inducing the differentiation into neurons including those with spinal motoneuron phenotype from hiPS cells [7].…”
Section: Induction Of Neural Differentiation Of Hips Cellsmentioning
confidence: 99%
“…Female C57BL/6 mice (5-12 weeks old, Japan SLC) were used as transplant recipients because we wanted to use genetically normal mice [7,8]. Animals were housed less than 5/cage with mouse food and water adlib on a 12/12 hr light/dark cycle.…”
Section: Experimental Scimentioning
confidence: 99%
See 3 more Smart Citations